Consequences of a Massive Refugee Influx on Firm Performance and Market Structure - Yusuf Emre Akgunduz; Yusuf Kenan Bagir; Seyit Mumin Cilasun; Murat Guray Kirdar (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
This study combines an administrative dataset of the full population of Turkish firms and the setting of the sudden mass migration of Syrian refugees to Turkey to identify the effect of migrants on firm performance and market structure. We find that economic activity increases in hosting regions, but negative implications exist for long-term productivity. As a result of the migrant shock, exiting firms expand and new firms are established; however, the resulting market structure shows less concentration. Quantitatively, a 10 percentage-point rise in the migrant-to-native ratio increases firm sales by 3.8% and the number of active firms by 5.8%, but reduces firms' average market share by 4.1%. We further document an increase in the export volume and variety of exported products to the Middle East and North Africa (MENA) region. In addition, a decline in export prices is observed, implying a rise in the competitiveness of exporting firms. We also uncover evidence for an effect of migrants' skills and networks on exports, as the export value and variety of products to the MENA region increase more than those to the EU region while the prices of products exported to the two regions show similar changes.
Keywords: J15; J61; F16; L11; 330; refugees; firm performance; market structure; sales; informality; exports; migrant business networks